GAS EJECTOR AS A PRESSURE STABILIZER AT THE INLET TO COMPRESSOR POWER INSTALLATION - Kulyk, M.S.; Kapitanchuk К.I.; Grekov, P.I.; Onischenko, S.P. (Proceedings of National Aviation University (archive), 2005)
Optimum supersonic gas ejector design procedure for application as pressure stabilizer at the inlet to compressor power installation is developed.